Village Financial System, Accountability, Transparency, and Sharia Economic Analysis - Fatmawati, Fatmawati; Semaun, Syahriyah; Astuti, An Ras Try; Muhammadun, Muzdalifah; Bahri, Andi (Universitas Muhammadiyah Makassar, 2025)
This research analyzes the Islamic Economic Analysis of Accountability and Transparency of the Village Financial System (SISKEUDES) in Cempa Pinrang District. The purpose of this research is to analyze the implementation of accountability, identify the level of transparency, and conduct an Islamic Economic Analysis of the Village Financial System (SISKEUDES) in Cempa Pinrang District. The research method used is descriptive qualitative. This type of research is field research. This research approach employs a case study approach. The data sources used are primary data in the form of direct interviews with village officials, the community, and secondary data in the form of books, journals, and articles related to the discussed topic. The results of this research show: 1). Overall, Siskeudes has successfully improved various aspects of accountability in village financial management, although it is important to continue monitoring it. This system encourages honesty and legal compliance, makes financial processes more orderly and easier to supervise, and makes the planning and implementation of village programs and policies more transparent with active support from the community and the BPD. 2). The transparency of Village Funds in Cempa Pinrang District is good in providing data. However, the main issue is that the community still has difficulty understanding information that is too technical and not all residents have equal access. Therefore, true transparency means that information must be easy to understand and accessible to everyone, so that accountability in the use of Village Funds can truly be realized3). Siskeudes has reinforced the principles of Islamic economics in village financial management: encouraging honesty (Siddiq) in data, enhancing responsibility (Amanah) through transparency and oversight, and honing the intelligence (Fathonah) of village officials in digital administration. However, the main challenge of Tabligh (information dissemination) is to ensure that transparent data can be easily understood and accessed by all layers of society, so that transparency truly empowers and encourages public participation.